THE EFFECT OF PROBLEM-BASED LEARNING MODEL ON HIGHER ORDER THINKING SKILLS IN CLASS IV ELEMENTARY SCHOOL SCIENCE LEARNING - Sukma Dwi Anggraini; Wahyu Susiloningsih (Media Inovasi Pendidikan dan Publikasi, 2024)
Thinking at a higher level requires decision making based on a thorough examination of the origins of the problem through the application of logic and reasoning. Higher-order thinking in students can be influenced by the application of the problem-based learning model. This study aims to examine how the problem-based learning model affects students' capacity for higher-order thinking in elementary school science subjects. It is a quantitative study using a True Experimental Design, specifically a Posttest-Only Control Design, involving 46 fourth-grade students 23 from Class IV A as the experimental group and 23 from Class IV B as the control group. The treatment involved using a problem-based learning model, and the data collection instrument was a higher-order thinking test with questions about the anatomical structure of plants. The Independent Samples Test t-test was used for data analysis. The study shows that elementary school students' ability to think critically increases when they use the problem-based learning approach in science learning. The results indicate that the problem-based learning model can improve students' understanding of the learning content and their capacity for higher-order thinking.